2014
DOI: 10.2174/18715273113126660153
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Disease and Type 2 Diabetes Mellitus: The Link to Tyrosine Hydroxylase and Probable Nutritional Strategies

Abstract: Alzheimer disease (AD) and type 2 diabetes mellitus (T2DM) are chronic health disorders that affect millions of people around the world. According to recent studies, there are molecular similarities in the inflammatory pathways involved in both AD and T2DM, which opens a new avenue for researchers with different perspectives to target the cause of these diseases rather than their obvious symptoms. Several links between inflammation, cardiovascular disease, T2DM and central nervous system disorders such as AD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…A possible role of the brain insulin resistance and a reduced insulin signaling in the AD's pathogenesis, was also described by several studies (Aliev et al, 2014 ). Baalba et al, by using streptozotocin-induced diabetic (STZ-T2DM) rats, showed that the daily intake of NSO induced the expression of insulin receptor and altered the expression of insulin-like growth factor-1 and phosphoinositide-3 kinase (Balbaa et al, 2016 ).…”
Section: Resultsmentioning
confidence: 65%
“…A possible role of the brain insulin resistance and a reduced insulin signaling in the AD's pathogenesis, was also described by several studies (Aliev et al, 2014 ). Baalba et al, by using streptozotocin-induced diabetic (STZ-T2DM) rats, showed that the daily intake of NSO induced the expression of insulin receptor and altered the expression of insulin-like growth factor-1 and phosphoinositide-3 kinase (Balbaa et al, 2016 ).…”
Section: Resultsmentioning
confidence: 65%
“…The brain insulin resistance may be due to peripheral insulin resistance, reduced insulin uptake by brain and elevated brain Aβ deposition [9]. Several studies investigated the role of insulin resistance and impaired insulin signaling in the AD pathogenesis in brain [10] and neuro-inflammation is mutual interaction between T2DM and AD [11]. Chronic inflammation in T2DM and the leaking of peripheral inflammatory mediators from T2DM to brain induces microglial activation and release of the inflammatory mediators IL-1β, IL-6 and TNF-α in brain [12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of factors have been proposed to cause age-induced damage to the brain, including oxidative stress, free radical damage, and intracellular fibrillary tangles, which can be modified by aging, and have been associated with occurrence of AD (Mohsenzadegan and Mirshafiey, 2012 ; Tatsumi et al, 2014 ). Moreover, DA deficiency was found to contribute to age-related changes (Aliev et al, 2014 ). Meanwhile, previous research showed that DA density progressively reduced with aging and more severely in cases with AD (Rieckmann et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%